Rido Experiences of Displaced Muslim Women: Basis of an Adaptive Coping Management Design Using CBT - Macabago, Jinky M. (Technium Social Sciences Journal, 2022)
Abstract. This study reported a qualitative phenomenological investigation of rido as experienced by displaced Muslim women. This inductive approach aimed to capture the richness and complexity of the lived experience of rido. These were verified and confirmed with the results of DSM-5 Self-Rated Level 1 Cross-Cutting Symptom Measure- Adult. Results showed three major themes and seven superordinate themes. These were Traumatic Events and Experiences as exemplified by Death of Loved Ones, Losses Due to Displacement, and Bloody Cycle of Retribution; Psychological Consequences that centered on Paranoia and Anxiety; and Coping Strategies exemplified by Psychological Resilience and Family Motivation. Results of DSM-5 Self-Rated Level 1 Cross-Cutting Symptom Measure-Adult showed that participants exhibited no significant and problematic symptoms that might warrant further assessment, treatment, or follow-up. A proposed CBT program was especially designed for this group in order to extend support to their predicament, help them recover, and ensure that they will have healthy psychological make-up and well-being.